Lipoprotein(a) As a Potential Predictive Factor for Earlier Aortic Valve Replacement in Patients with Bicuspid Aortic Valve - Aleksandra Krzesińska; Maria Nowak; Agnieszka Mickiewicz; Gabriela Chyła-Danił; Agnieszka Ćwiklińska; Olga M. Koper-Lenkiewicz; Joanna Kamińska; Joanna Matowicka-Karna; Marcin Gruchała; Maciej Jankowski; Marcin Fijałkowski; Agnieszka Kuchta (Biomedicines, 2023)
Bicuspid aortic valve (BAV) affects 0.5–2% of the general population and constitutes the major cause of severe aortic valve stenosis (AVS) in individuals ≤70 years. The aim of the present study was to evaluate the parameters that may provide information about the risk of AVS developing in BAV patients, with particular emphasis on lipoprotein(a) (Lp(a)), which is a well-recognized risk factor for stenosis in the general population. We also analyzed the impact of autotaxin (ATX) and interleukin-6 (IL-6) as parameters potentially related to the pathomechanism of Lp(a) action. We found that high Lp(a) levels (>50 mg/dL) occurred significantly more frequently in patients with AVS than in patients without AVS, both in the group below and above 45 years of age (p = 0.036 and p = 0.033, respectively). Elevated Lp(a) levels were also strictly associated with the need for aortic valve replacement (AVR) at a younger age (p = 0.016). However, the Lp(a) concentration did not differ significantly between patients with and without AVS. Similarly, we observed no differences in ATX between the analyzed patient groups, and both ATX activity and concentration correlated significantly with Lp(a) level (R = 0.465, p < 0.001 and R = 0.599, p < 0.001, respectively). We revealed a significantly higher concentration of IL-6 in young patients with AVS. However, this observation was not confirmed in the group of patients over 45 years of age. We also did not observe a significant correlation between IL-6 and Lp(a) or between CRP and Lp(a) in any of the analyzed groups of BAV patients. Our results demonstrate that a high level of Lp(a), greater than 50 mg/dL, may be a significant predictive factor for earlier AVR. Lp(a)-related parameters, such as ATX and IL-6, may be valuable in providing information about the additional cardiovascular risks associated with developing AVS.